Analysis of The Effect of Product Quality, Price, and Service Quality on Consumer Purchase Intention in The Traditional Market of Medan (A Case Study of Inpres Kwala Bekala Market, Medan) - Aginta, Windy; Muda, Iskandar; Silalahi, Amlys Syahputra (Universitas Pahlawan Tuanku Tambusai, 2023)
The research aims to determine and analyze the influence of product quality, price, and service quality on consumer purchase intention in the traditional market of Medan, specifically in Inpres Kwala Bekala Market, Medan. The research method used a quantitative approach, which involves examining the relationship between two or more variables. The study intends to investigate the extent to which the independent variables, consisting of Product Quality and Service Quality, influence the dependent variable, which is Purchase Intention, while the intervening variable used is Price.Data collection was conducted using a questionnaire in the form of a survey and documentary study. The data analysis method employed was Structural Equation Model (SEM) analysis, using the Analysis of Moment Structure (AMOS) computer program. The research findings indicated that Product Quality has a negative and insignificant influence on Price. This means that Product Quality does not play a significant role in shaping the Price. Service Quality has a positive and significant influence on Price, indicating that the implementation of Service Quality can affect the fluctuation of prices. Price has a positive and significant influence on Purchase Intention. This implies that price increases or decreases can impact consumer purchase intention. Product Quality has a positive and significant influence on Purchase Intention, meaning that the implementation of Product Quality can affect the level of consumer purchase intention. Service Quality has a positive and significant influence on Purchase Intention, indicating that Service Quality contributes to increasing consumer purchase intention. Keyword: Location, Product Diversity, Price, Service Quality